2014
DOI: 10.30843/nzpp.2014.67.5750
|View full text |Cite
|
Sign up to set email alerts
|

A volatile compound 2undecanone increases walking but not flying tomato potato psyllid movement toward an odour source

Abstract: Bactericera cockerelli (tomato potato psyllid; TPP) is an important pest of solanaceous crops in New Zealand and North America A volatile compound that alters the behaviour of TPP could be developed into a component of an integrated pest management strategy for solanaceous crops One compound 2undecanone was found to increase the percentages of female and male TPP (65 P

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…27 indicate that 2-decanone is involved in attracting the parasitoids Dendrosoter protuberans and Cheiropachus quadrum to their host Phloeotribus scarabaeoides . Some studies have revealed the role played by 2-undecanone in an integrated pest management strategy for tomato 28 and solanaceous crops, the latter due to its capacity to alter Bactericera cockerelli behavior 29 . However, other studies have also shown that 2-undecanone emissions do not differ between Brassica rapa plants exposed/not exposed by Pieris brassicae to leaf herbivory 30 .…”
Section: Discussionmentioning
confidence: 99%
“…27 indicate that 2-decanone is involved in attracting the parasitoids Dendrosoter protuberans and Cheiropachus quadrum to their host Phloeotribus scarabaeoides . Some studies have revealed the role played by 2-undecanone in an integrated pest management strategy for tomato 28 and solanaceous crops, the latter due to its capacity to alter Bactericera cockerelli behavior 29 . However, other studies have also shown that 2-undecanone emissions do not differ between Brassica rapa plants exposed/not exposed by Pieris brassicae to leaf herbivory 30 .…”
Section: Discussionmentioning
confidence: 99%